The 6 most important decisions you'll ever make : a guide for teens - Covey, Sean. (New York : Fireside, 2006)
Describes six important decisions teenagers will face and offers advice on the choices that should be made, discussing school, friends, parents, dating and sex, addictions, and self-worth.
"A Fireside Book.".
Includes bibliographical references (p. 310-311) and index.
School Library Journal.
Young Adult
Keywords: Decision making in adolescence; Teenagers -- Life skills guides; Teenagers -- Conduct of life; Decision making; Teenagers -- Life skills guides; Teenagers -- Conduct of life